The Legality of the Threat or Use of Nuclear Weapons According to the Advisory Opinion of the International Court of Justice - أحمد حميد عجم البدري م. د. (lark, 2021)
The United Nations General Assembly passed a resolution at its 49th session requesting an advisory opinion from the International Court of Justice on the threat or use of nuclear weapons in any scenario under international law. The court’s response to the fatwa created many issues, the most serious of which was the court’s finding that it couldn’t make a definitive verdict on the legality or illegality of a country’s deployment of nuclear weapons in an extreme situation of self-defense where its survival was at threat. This research will also look into the court’s jurisdiction in responding to the General Assembly’s fatwa request, look into the relevant legal texts, and look into the jurisprudence and opinions surrounding the fatwa given by the court judges.